Sedative-hypnotic Binding to 11β-hydroxylase. (November 2016) - Pejo, Ervin; Zhou, Xiaojuan; Husain, S. Shaukat; Raines, Douglas E.
Abstract : Background: Etomidate potently suppresses adrenocortical steroid synthesis with potentially deleterious consequences by binding to 11β-hydroxylase and inhibiting its function. The authors hypothesized that other sedative-hypnotics currently in clinical use or under development (or their metabolites) might bind to the same site at clinically relevant concentrations. The authors tested this hypothesis by defining etomidate's affinity for this site and the potencies with which other sedative-hypnotics (and their metabolites) inhibit etomidate binding. Methods: 3 H-etomidate's binding to adrenal membranes from Sprague-Dawley rats was characterized with a filtration assay, and its dissociation constant was defined using saturation and homologous ligand competition approaches. Half-inhibitory concentrations of sedative-hypnotics and metabolites were determined from the reduction in specific 3 H-etomidate binding measured in the presence of ranging sedative-hypnotic and metabolite concentrations. Results: Saturation and homologous competition studies yielded 3 H-etomidate dissociation constants of 40 and 21 nM, respectively. Half-inhibitory concentrations of etomidate and cyclopropyl methoxycarbonyl metomidate (CPMM) differed significantly (26 vs. 143 nM, respectively; P < 0.001), and those of the carboxylic acid (CA) metabolites etomidate-CA and CPMM-CA were greater than or equal to 1, 000× higher than their respective parent hypnotics. The half-inhibitory concentration of dexmedetomidine was 2.2 µM, whereas those of carboetomidate, ketamine, and propofol were greater than or equal to 50 µM. Conclusion: Etomidate's in vitro dissociation constant for 11β-hydroxylase closely approximates its in vivo adrenocortical half-inhibitory concentration. CPMM produces less adrenocortical suppression than etomidate not only because it is metabolized faster but also because it binds to 11β-hydroxylase with lower affinity. Other sedative-hypnotics and metabolites bind to 11β-hydroxylase and inhibit etomidate binding only at suprahypnotic concentrations. Abstract : The in vitro dissociation constant of etomidate for 11β-hydroxylase is approximately 30 nM, which is nearly two orders of magnitude lower than its hypnotic concentration. Cyclopropyl methoxycarbonyl metomidate produces less adrenocortical suppression than etomidate because it is metabolized faster and binds to 11β-hydroxylase with lower affinity. The carboxylic acid metabolites of etomidate and cyclopropyl methoxycarbonyl metomidate bind to 11β-hydroxylase with affinities that are at most 1% that of their parent hypnotics. Carboetomidate, dexmedetomidine, ketamine, and propofol do not suppress adrenocortical function at hypnotic concentrations because they bind to 11β-hydroxylase with very low affinities.